Kemampuan Literasi dan Kepercayaan Diri Siswa SMP Berdasarkan Akreditasi Sekolah Swasta dan Negeri di Kota Singkawang - Zulfahita Zulfahita; Nurul Husna; Sri Mulyani (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This study aims to describe literacy skills, both mathematical literacy, and language literacy, as well as the self-confidence of junior high school students based on public and private school accreditation. The research method used was a descriptive qualitative. The subjects of this study consisted of 169 students from 7 randomly selected schools. The instruments used were mathematical literacy questions, language literacy questions, and self-confidence questionnaires which were supported by interviews. The data analysis technique used qualitative descriptive analysis. Based on the results of data analysis, it can be concluded: (1) Mathematical literacy skills at state schools with A accreditation were sufficiently able to apply the processes of communication literacy, representation, reasoning, and arguments, devising strategies for solving problems, symbols and formalism. Mathematical literacy at state schools with B accreditation was quite capable of implementing the Mathematising Representation literacy process and devising strategies for solving problems. Mathematical literacy in private schools with A accreditation was quite capable of implementing the devising strategies for solving problems literacy process. And, Mathematical literacy in private schools with B accreditation was quite capable of implementing the communication literacy process. (2) Language literacy skills in public and private schools with A and B accreditation showed the same ability. (3) The self-confidence level of students, both public and private schools based on accreditation A and B, was in the sufficient category, and contributed to students confidence and the quality of education.